2013
DOI: 10.1177/0891988713516542
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Longitudinal Electroconvulsive Therapy

Abstract: Electroconvulsive therapy (ECT) is the most effective treatment for a depressive episode but the mechanism of action and neural correlates of response are poorly understood. Different theories have suggested that anticonvulsant properties or neurotrophic effects are related to the unique mechanism of action of ECT. This review assessed longitudinal imaging investigations (both structural and functional) associated with ECT response published from 2002 to August 2013. We identified 26 investigations that used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 53 publications
0
52
0
2
Order By: Relevance
“…Concurrently with the compromised long-range connectivity, BTBR mice exhibit aberrant intrahemispheric connectivity as identified by diffusion tensor imaging [20], which is another widely acknowledged attribute of the autistic brain [47]. With this regard, ECT was shown to reduce local connectivity in prefrontal cortex [29], an effect which, if experimentally confirmed, could explain, at least in part, its therapeutic effect in BTBR mice. At the same time, it is highly plausible that mechanisms of beneficial effects of ECT in autism (much like in the discussed psychiatric disorders) cannot be deduced to a single pathway or a molecule but rather involve a variety of targets.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Concurrently with the compromised long-range connectivity, BTBR mice exhibit aberrant intrahemispheric connectivity as identified by diffusion tensor imaging [20], which is another widely acknowledged attribute of the autistic brain [47]. With this regard, ECT was shown to reduce local connectivity in prefrontal cortex [29], an effect which, if experimentally confirmed, could explain, at least in part, its therapeutic effect in BTBR mice. At the same time, it is highly plausible that mechanisms of beneficial effects of ECT in autism (much like in the discussed psychiatric disorders) cannot be deduced to a single pathway or a molecule but rather involve a variety of targets.…”
Section: Discussionmentioning
confidence: 98%
“…ECT represents an effective treatment of pharmacoresistant cases of depression [29][30][31], bipolar disorder [32], and schizophrenia [33,34]. Mechanisms underlying the therapeutic effects of ECT remain largely elusive, with 2 major hypotheses dominating: the anticonvulsant, whereby the effects are attributed to the increase of seizure threshold and decrease of seizure duration observed during the course of ECT [35], and the neurotrophic, which brings in the induction of several neurotrophic factors (e.g., brain-derived neurotrophic factor, vascular endothelial growth factor), transcription factors (e.g., cfos), and neurogenesis as explanations [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In a review article, Abbott et al (2014a) showed that ECT "anticonvulsant effects appear to be predominately frontally mediated and neurotrophic effects appear to be focused on the medial temporal lobes". The same group also detected a connectivity and volume increase in the hippocampal area (Abbott et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Using the ECT review of Abbott et al (2014a) showing excess activity in MTL and lacking activity in the frontal lobes I suggest that STM Control is overworked trying to establish stable patterns in LTM. It could be that the confusion resulting from ECT is due to the failure of this process, suggesting a neurological definition of confusion.…”
mentioning
confidence: 99%
“…This is particularly the case for neurostimulation techniques such as repetitive transcranial magnetic stimulation (rTMS) 21 or ECT. 1,12,66,92 For example, rTMS to the dorsolateral prefrontal cortex may be effective in depression through long-term plasticity induction, leading to a reduction of the hyperconnectivity of the default mode network and a restoration of connectivity in a frontoparietal network. Similarly, the effect of deep brain stimulation (DBS) is predicted by connectomics and may be mediated by white matter.…”
Section: Toward Individually Targeted Psychosurgerymentioning
confidence: 99%